2013
DOI: 10.3389/fneur.2013.00080
|View full text |Cite
|
Sign up to set email alerts
|

“Sightblind”: Perceptual Deficits in the “Intact” Visual Field

Abstract: Unilateral visual cortex lesions caused by stroke or trauma lead to blindness in contralateral visual field – a condition called homonymous hemianopia. Although the visual field area processed by the uninjured hemisphere is thought to be “intact,” it also exhibits marked perceptual deficits in contrast sensitivity, processing speed, and contour integration. Such patients are “sightblind” – their blindness reaches far beyond the primary scotoma. Studies showing perceptual deficits in patients’ intact fields are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 37 publications
6
27
0
2
Order By: Relevance
“…Interestingly, a previous report on the same cohort of patients showed similar improvements for both the perimetric defect and intact VF (Elshout et al, 2016), which suggest that also in the intact parts of the VF clinically relevant improvements can be obtained. This complements various reports that show perceptual deficits in the "intact" parts of the VF (for review: Bola et al, 2013;Cavézian et al, 2015;Clatworthy et al, 2013; Geuzebroek and van den Berg, 2017). Furthermore, is has been suggested that this observation partially accounts for the subjective visual impairment as experienced by the patients and should therefore also be considered when examining VRT effects (Bola et al, 2013).…”
Section: Full Field Improvement Following Vrtsupporting
confidence: 86%
“…Interestingly, a previous report on the same cohort of patients showed similar improvements for both the perimetric defect and intact VF (Elshout et al, 2016), which suggest that also in the intact parts of the VF clinically relevant improvements can be obtained. This complements various reports that show perceptual deficits in the "intact" parts of the VF (for review: Bola et al, 2013;Cavézian et al, 2015;Clatworthy et al, 2013; Geuzebroek and van den Berg, 2017). Furthermore, is has been suggested that this observation partially accounts for the subjective visual impairment as experienced by the patients and should therefore also be considered when examining VRT effects (Bola et al, 2013).…”
Section: Full Field Improvement Following Vrtsupporting
confidence: 86%
“…Indeed, previous studies demonstrated that patients with localized vision loss (scotoma) experience perceptual impairments even in the intact visual field areas distant from the scotoma. Specifically, the areas considered to be "intact" based on the perimetry results actually exhibit subtle perceptual deficit in the processing speed (Bola et al, 2013b;Poggel et al, 2011;Cavezian et al, 2010) and contour integration (Paramei and Sabel, 2008;Schadow et al, 2009). These subtle deficits in the "intact" field are "sightblind" (review: Bola et al, 2013a), as they are the flip-side of "blindisight" where subtle residual vision exists deep in the "blind" field.…”
Section: Network Synchronization and Perception: "Sightblindness"mentioning
confidence: 97%
“…However, the visual impairment is not restricted to scotomata but is actually more widespread, with additional, more subtle deficits in the presumed “healthy” hemisphere (the “intact” visual field), as indicated by tests of reaction time and perceptual completion. This phenomenon has been termed “sightblindness” [10,11]. These findings lead to the suggestion that the effects of a unilateral visual cortex lesion are not just affecting the damaged hemisphere, but rather the visual neural network is disturbed with its different subcortical, cortical, and interhemispheric loops [12,13].…”
Section: Introductionmentioning
confidence: 99%